Book Review: Bruce Nussbaum, Creative Intelligence: Harnessing the Power to Create, Connect, and Inspire. (June 2017) - Mishra, Subhendu
Bruce Nussbaum, Creative Intelligence: Harnessing the Power to Create, Connect, and Inspire, 2013, New York: Harper Collins, 351 pp., US$22.89. ISBN: 978-0-06-229280-3